A photochromic upconversion nanoarchitecture: towards activatable bioimaging and dual NIR light-programmed singlet oxygen generation. Issue 44 (29th October 2019) - Mi, Yongsheng; Cheng, Hong-Bo; Chu, Hongqian; Zhao, Jian; Yu, Mingming; Gu, Zhanjun; Zhao, Yuliang; Li, Lele
Abstract : A novel upconversion nanoarchitecture is designed, whose 980 nm light photosensitized activity could be activated by 808 nm light. Abstract : The precise control of singlet oxygen ( 1 O2 ) generation is in great demand for biological studies and precision medicine. Here, a nanoarchitecture is designed and synthesized for generating 1 O2 in a dual NIR light-programmable manner, while shifting to the therapeutic window. The nanoarchitecture is constructed by controlled synthesis of mesoporous silica-coated upconversion nanoparticles (UCNPs), wherein the porphyrin photosensitizers (PSs) are covalently embedded inside the silica walls while NIR (808 nm)-responsive diarylethene (DAE) photochromic switches are loaded in the nanopores. Upon irradiation with 980 nm NIR light, the UCNP core absorbs low energy photons and transfers energy to the PSs in the silica wall, leading to efficient 1 O2 generation. Furthermore, this 980 nm NIR light photosensitized activity can be remotely controlled by irradiation with a distinct NIR wavelength (808 nm). The 1 O2 generation is inhibited when the DAE installed in the nanopores is in the closed form, whereas irradiation of the nanoconstruct with 808 NIR light leads to the transformation of DAE to the open form, and thus enabling full recovery of the 980 nm NIR light excited 1 O2 generation capability. The NIR light-mediated on-demand "activation" of the nanoarchitecture for bioimaging and controllable photodynamic therapy is further demonstrated in vitro and in vivo .